PPTTG Pemipil Jagung untuk Petani Jagung Bandar Klippa Kecamatan Percut Sei Tuan - Sitorus, Melvin; Kamil, Idham; Tarigan, Jenny Sari; Benar, Benar (Yayasan Cita Cendikiawan Al Kharizmi, 2022)
Bandar Klippa Village is one of the villages in Percut Sei Tuan sub-district, Deli Serdang Regency, North Sumatra Province with an area of ​​1,828.4 Ha. In the village of Bandar Klippa, most of the agricultural land out of a total of 575 hectares is planted with corn with an average yield per hectare of 20 tons if there is sufficient rainfall. Generally, corn farmers immediately sell their crops to the factory after they have been harvested. The price of corn if it is sold directly to the factory is around 2800/kg, namely whole corn and the corn cob because the farmers do not yet have a corn sheller. If shelling is done, the price of corn increases to IDR 4,200/kg or almost 2 times that. This service is intended to help corn farmers get added value to their corn yields by providing a corn sheller machine designed by the proposing team and providing training in the use and maintenance of the sheller machine so that it can be used for a long time. After being crushed, the corncobs can also be sold to cattle breeders at a price of around Rp. 1000 to Rp. 2000 for each kilogram. The sheller machine can shell 350 kg of corn every hour